THE ORTHOGRAPY OF KARAITE HEBREW BIBLE MANUSCRIPTS IN ARABIC TRANSCRIPTION - Khan, Geoffrey (Journal of Semitic studies, 1993)
GEOFFREY KHAN; THE ORTHOGRAPY OF KARAITE HEBREW BIBLE MANUSCRIPTS IN ARABIC TRANSCRIPTION1, Journal of Semitic Studies, Volume XXXVIII, Issue 1, 1 March 1993, P